2021
DOI: 10.1111/obr.13275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training with and without caloric restriction on visceral fat: A systemic review and meta‐analysis

Abstract: Summary We performed a systematic review and meta‐analysis to investigate the effect of resistance training (RT) with and without caloric restriction (CR) on visceral fat (VF). PubMed and Scopus were searched to identify original articles published through December 2020. Standardized mean differences and 95% confidence intervals (95% CIs) were determined, and separate analyses were conducted for RT versus control, and RT plus CR versus CR only. Thirty‐four studies including 38 intervention arms and involving 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 96 publications
2
17
1
1
Order By: Relevance
“…In the study of Maillard et al, 11 for example, high‐intensity interval training was associated with a reduction in VAT of ~0.2 SMD in adults with overweight/obesity. Likewise, general aerobic exercise promoted a reduction in VAT of ~0.3 SMD, as observed in the study of Ismail et al 8 A potential explanation for the different findings reported previously, 8–12 and this study could be related to the additional effect derived from combined resistance and aerobic exercise, resulting in a higher effect on VAT and SAT. Therefore, even without a dietary intervention, combined resistance and aerobic exercise can significantly reduce abdominal fat with greater effects than interventions comprising only aerobic exercise modalities, 8,11 previously deemed the most effective modality for reducing overall abdominal fat.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the study of Maillard et al, 11 for example, high‐intensity interval training was associated with a reduction in VAT of ~0.2 SMD in adults with overweight/obesity. Likewise, general aerobic exercise promoted a reduction in VAT of ~0.3 SMD, as observed in the study of Ismail et al 8 A potential explanation for the different findings reported previously, 8–12 and this study could be related to the additional effect derived from combined resistance and aerobic exercise, resulting in a higher effect on VAT and SAT. Therefore, even without a dietary intervention, combined resistance and aerobic exercise can significantly reduce abdominal fat with greater effects than interventions comprising only aerobic exercise modalities, 8,11 previously deemed the most effective modality for reducing overall abdominal fat.…”
Section: Discussionsupporting
confidence: 72%
“…Consequently, this precludes identifying the potential use of resistance training in individuals with overweight/obesity. Moreover, despite previous systematic reviews investigating exercise and dietary effects on body composition [4][5][6][7] and visceral adipose tissue, [8][9][10][11][12] the specific effects of resistance exercise on fat mass and lean mass have not been investigated in depth in those overweight/obese. For instance, it is not well understood if resistance exercise, alone or combined with other exercise components and dietary interventions, results in meaningful effects on fat mass while maintaining or increasing lean mass in this population.…”
Section: Introductionmentioning
confidence: 99%
“…1 2 In brief, meta-analyses and systematic reviews of controlled clinical exercise studies show that MSE leads to enhanced cardiometabolic, 3 musculoskeletal 4 and mental health, 5 and reductions in visceral fat. 6 Recent data from prospective cohort studies suggest that MSE is independently associated with a reduced risk of all-cause and disease-specific mortality, 7 8 cardiovascular disease, 9 type 2 diabetes, 10 11 obesity 12 13 and some cancers. 8 Despite its multiple independent health benefits, and the fact that MSE was first included as part of the US physical activity guidelines in 2008, 14 and global guidelines since 2010, 15 in comparison to moderate-tovigorous aerobic physical activity (MVPA: eg, walking, running or cycling) and sedentary behaviour (low energy sitting, reclining or lying posture in waking hours), this exercise modality has received little attention in physical activity epidemiology.…”
Section: Introductionmentioning
confidence: 99%
“… 1 2 In brief, meta-analyses and systematic reviews of controlled clinical exercise studies show that MSE leads to enhanced cardiometabolic, 3 musculoskeletal 4 and mental health, 5 and reductions in visceral fat. 6 Recent data from prospective cohort studies suggest that MSE is independently associated with a reduced risk of all-cause and disease-specific mortality, 7 8 cardiovascular disease, 9 type 2 diabetes, 10 11 obesity 12 13 and some cancers. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation